Exploring the Impact of Hexagon Fraud Theory on Fraud Tendencies among Regional Work Unit Employees in Bandung City: A Quantitative Analysis - Andini Dwiyanti; Nunuy Nur Afiah; Ivan Yudianto (Journal of Accounting Auditing and Business, 2023)
This research aimed to analyze the effect of the hexagon fraud theory on fraud tendencies based on the perceptions of regional work unit employees in Bandung City. This research used a quantitative approach. The sample was 364 regional work unit employees in Bandung City. A simple random sampling method was used in this research. Data were analyzed using multiple linear regression. The results of this research indicated that the variables of distributive justice (proxy of stimulus), collusion, and internal control (proxy of opportunity) have a negative and significant effect on fraud tendencies. Meanwhile, the variables of leadership style (proxy of capability), organizational commitment (proxy of rationalization), and individual morality (proxy of ego) do not affect fraud tendencies.